ANTITHROMBOTIC THERAPY OF ISCHEMIC HEART DISEASE: FROM FAST ACTING ANTIAGGREGANTS TO STATINES AND NITRATE OXIDE. IS IT REAL? - I. A. Latfullin; A. A. Podolskaya (Рациональная фармакотерапия в кардиологии)
Mechanisms of atherothrombosis in atherosclerosis of coronary arteries are described. Mechanism of action and clinical efficiency of antithrombotic and antiplatelet medicines such as acetylsalicylic acid, warfarin, ticlopidine and clopidogrel are discussed. Study data on new antiplatelet drugs are given: selective thromboxane inhibitors, antagonists of thromboxane receptors, blockers of platelet receptors for glycoproteins GPIIb/IIIa. Possibility of clinical use of additional antiplatelet features of statines is discussed, as well as their connection to stimulation of nitrate oxide production, powerful endogenous antiplatelet factor. Examples of other donators of nitrate oxide and activators of its endogenous synthesis are given.